Precisiones de Tomás de Aquino en torno a la noción de concordia política (homónoia) de Aristóteles - Undurraga, Sebastián Buzeta (Sapientia, 2014)
This article is intended to clarify some aspects that seem central to the contribution of Aquinas to Aristotle’s notion of homónoia. In such a way that, firstly, the contributions and the deepening of the Angelic homónoia concept or concord, mainly through identifying the accuracy between concord and justice; and, secondly, understanding concord as an efficient cause of the State or political association.